Unit Roots, Polynomial Transformations and the Environmental Kuznets Curve - Gang Liu; Terje Skjerpen; Anders Rygh Swensen; Kjetil Telle (Statistics Norway, Research Department, 2006)
Time-series regressions including non-linear transformations of an integrated variable are not uncommon in various fields of economics. In particular, within the Environmental Kuznets Curve (EKC) literature, where the effect on the environment of income levels is investigated, it is standard procedure to include a third order polynomial in the income variable. When the income variable is an I(1)-variable and this variable is also included nonlinearly in the regression relation, the properties of the estimators and standard inferential procedures are unknown. Surprisingly, such problems have received rather limited attention in applied work, and appear disregarded in the EKC literature. We investigate the properties of the estimators of long-run parameters using Monte-Carlo simulations. We find that the mean of the ordinary least squares estimates are very similar to the true values and that standard testing procedures based on normality behave rather well.
Keywords: C15; C16; C22; C32; O13; 330; Emissions; Environmental Kuznets Curve; Unit Roots; Monte Carlo Simulations